Examining the contributions of syntactic awareness and syntactic knowledge to reading comprehension. (14th April 2015) - Brimo, Danielle; Apel, Kenn; Fountain, Treeva
Abstract : Purpose: The purpose of this study was to examine the effect(s) of syntactic knowledge and syntactic awareness on adolescents' reading comprehension. Method: One hundred and seventy‐nine, 9th and 10th grade students' syntactic awareness, syntactic knowledge and reading comprehension skills were assessed. In addition, other known contributors to reading comprehension were assessed including word level reading, short‐term memory and vocabulary knowledge skills. Results: Path analysis was used to analyse the direct and indirect effects of syntactic awareness and syntactic knowledge on reading comprehension. Students' syntactic knowledge directly accounted for significant variance in reading comprehension. Syntactic awareness indirectly accounted for significant variance in reading comprehension through syntactic knowledge. Conclusions: This study confirmed the significant effects of syntactic knowledge and syntactic awareness on reading comprehension among adolescent students. This is one of the very few studies to examine both knowledge and awareness of syntax simultaneously and to determine that syntactic knowledge mediates the contribution of syntactic awareness to adolescent students' reading comprehension.